The impact of innovation and renewable energy on CO2 emission in Asian developing countries - Pham, Xuan Truong; Nguyen, Cam Nhung; Nguyen, Thi An Ly (Journal of International Economics and Management, 2024)
This study examines the impact of innovation and renewable energy on CO2 emissions in a sample of 15 developing Asian countries from 2000 to 2020. Using panel data regression analysis, it identifies two key findings. First, innovation - measured by research and development (R&D) expenditures and the number of patents - leads to an increase in CO2 emissions, likely driven by the scale effect, whereby economic growth and technological advancements initially result in higher emissions. Second, a higher share of renewable energy consumption significantly reduces emissions, underscoring the critical role of clean energy in mitigating environmental impacts. The findings also support the Environmental Kuznets Curve (EKC) hypothesis, suggesting that as income levels rise, emissions initially grow but eventually decline as economies transition toward greener technologies. Additionally, the study highlights population growth and afforestation as significant factors influencing CO2 emissions. By offering empirical evidence, this research provides valuable guidance for policymakers in developing Asian nations, emphasizing the need to balance innovation with greater investments in renewable energy to achieve sustainable development and lower carbon emissions.​